The Delivery of RNA-Interference Therapies Based on Engineered Hydrogels for Bone Tissue Regeneration - Yu, Tingting; Wang, Hufei; Zhang, Yunfan; Wang, Xing; Han, Bing (Frontiers in Bioengineering and Biotechnology, 2020)
RNA interference (RNAi) is an efficient posttranscriptional gene modulation strategy mediated by small interfering RNAs (siRNAs) and microRNAs (miRNAs). Since its discovery, RNAi has been utilized extensively to diagnose and treat diseases at both the cellular and molecular levels. However, the application of RNAi therapies in bone regeneration has not progressed to clinical trials. One of the major challenges for RNAi therapies is the lack of efficient and safe delivery vehicles that can actualize sustained release of RNA molecules at the target bone defect site and in surrounding cells. One promising approach to achieve these requirements is encapsulating RNAi molecules into hydrogels for delivery, which enables the nucleic acids to be delivered as RNA conjugates or within nanoparticles. Herein, we reviewed recent investigations into RNAi therapies for bone regeneration where RNA delivery was performed by hydrogels.